Kajian hukum Islam terhadap BPJS berdasarkan pendapat para ulama dan fiqih kontemporer - billah, ahmad nastain (Maliki Interdisciplinary Journal, 2026)
This article discusses the study of Islamic law on BPJS based on the opinions of scholars and contemporary fiqh, with a focus on analyzing legal status, the sharia principles involved, as well as considerations of benefit and harm in modern social security practices. This research departs from the debate among scholars regarding the permissibility of the BPJS social insurance scheme, especially related to issues of contract, potential riba, gharar, and elements of takaful (mutual assistance) within its system. Through a qualitative approach based on literature study, this article compares the opinions of classical scholars, contemporary scholars, MUI fatwas, as well as the views of modern fuqaha who see BPJS as a public necessity in the context of health protection. The results of the study show that most contemporary scholars tend to allow BPJS on the grounds of emergency, necessity, and the existence of the principle of public benefit, although improvements are still needed in elements that are not yet fully in accordance with sharia. This article concludes that BPJS in principle can be accepted in the perspective of Islamic law as long as it is directed toward a social security system that is more transparent, free from usurious practices, and oriented toward justice and mutual assistance. This finding is expected to serve as a reference for the development of health insurance policies that are more in line with sharia principles.